Design Of Toyota Home Service Applications For AUTO2000 Based On Android - Aswin, Arief Rahmadian (Jurnal Sains dan Informatika, 2016)
AUTO2000 is a network of sales services, maintenance, repair and supply of spare parts Toyota that was established in 1975 under the name Astra Motor Sales, in 1989 changed its name to AUTO2000 with management that has been handled entirely by PT. Astra International Tbk. Services provided by AUTO2000 one of which is a service of Toyota Home Service, a service provided by the service vehicle Auto 2000 where customers can service their vehicles without having to come to the dealership Auto 2000. At this service the customer usually make bookings in advance by registering perform via telephone, and come directly to the dealer AUTO2000. To create the service quality vehicle service, in to customer needs and satisfaction. By utilizing the development of technologi it is necessary to design an android based mobile application that is able to provide services more effectively and efficiently to customers in registering and booking services Toyota Home Service at AUTO2000.